(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
Between March 16th and October 2nd, 2020, 202 different scenes of the Maria Cláudia doll were posted on two social networks daily, making the miniature the best in the real world. Ludic took the space that cannot be touched and/or measured. The article approaches the animation theater performed in digital media, as well its repercussions in times of the Covid-19 pandemic, marked by changes in everyday life, social isolation, frustrations, emotional losses, grief. It concludes that, by aiming at the universe of playfulness, the virtual space has become a place of cognitive development, but also of resistance and struggle for sanity, beauty, life and culture.